The Effect Of Edmodo On Students’ Willingness To Communicate, Intrinsic Motivation And Self-Confidence Of SMKN 4 Kendari - Rahmawati Kahar, Siti; Hanafi, Hilaluddin; Alberth, Alberth (Halu Oleo University, 2016)
This study puts an emphasis on the use of edmodo as a form of computer-assisted langauge learning activity, investigating its effects on willingness to communicate (WTC), intrinsic motivation and self-confidence in learning English. The total number of participants involved was 27 students of X TKJ B in SMKN 4 Kendari. Quantitave data originated from close ended questionnaire, while open ended questionnaire used as qualitative data. Paired sample t-test was employed to seek the effect of social media on students’WTC, intrinsic motivation and self-confidence. The result shows that there is no significant effect edmodo on students’WTC, intrinsic motivation and self-confidence before and after did treatment. In contast, the result of open ended questionnaire reports that edmodo may give postive impact on their WTC, intrinsic motivation and self-confidence. These different results affected by some factors namely, students’perception of edmodo, technology, language skills characteristic and design of learnig activities.